Asset Pricing in a Generalized Mean-Lower Partial Moment Framework: Theory and Evidence - Harlow, W. V.; Rao, Ramesh K. S. (Journal of Financial and Quantitative Analysis, 1989)
W. V. Harlow, Ramesh K. S. Rao, Asset Pricing in a Generalized Mean-Lower Partial Moment Framework: Theory and Evidence, The Journal of Financial and Quantitative Analysis, Vol. 24, No. 3 (Sep., 1989), pp. 285-311